1, 2-Addition to trifluoromethylated β-enamino diketones: regioselective synthesis of trifluoromethyl-containing azomethine pyrazoles and isoxazoles. Issue 13 (20th March 2020) - Pianoski, Karlos Eduardo; Poletto, Julia; Vieira da Silva, Michael Jackson; Ascencio Camargo, Jeniffer Nascimento; Jacomini, Andrey Petita; Gonçalves, Davana Silva; Back, Davi Fernando; Moura, Sidnei; Rosa, Fernanda Andreia
Abstract : Trifluoromethylated β-enamino diketones undergo type 1, 2-addition leading to regioselective synthesis of trifluoromethylated azoles containing an azomethine group. Abstract : A simple and efficient methodology for highly regioselective synthesis of azomethine pyrazoles and isoxazoles containing a trifluoromethyl group is reported. The cyclocondensation of trifluoromethylated β-enamino diketones (TBED) with phenylhydrazine and hydroxylamine hydrochloride, in the presence of BF3, provided 5-aryl-4-[( tert -butyl)iminomethyl]-3-trifluoromethylazoles by aza-Michael-type 1, 2-addition. The scope of the reaction was expanded by transimination with arylamines in a one-pot method starting from TBED. Thus, 83 novel 4-[(alkyl/aryl)iminomethyl]-3-trifluoromethylazoles were obtained with high regioselectivity and in yields of 51 to 89%.